Manajemen Pembiayaan Sekolah dan Madrasah - Asynul Zumarti; Ali Amran; Mudasir Mudasir; Abdullah Syarif (At-Tajdid : Journal of Islamic Studies, 2022)
This research aims to analyze the financing management of schools and madrasas. This research is a literature review research with a descriptive approach. The data was obtained from a literature review derived from books and journals of school and madrasah financing management. Data analysis by reducing data, displaying data and drawing conclusions. The findings in this study are education financing related to the analysis of financing sources, distribution/allocation, and the system or mechanism of financial management which focuses on three components, namely planning, accounting, and auditing..